Three-spined stickleback Gasterosteus aculeatus, as a possible paratenic host for salmonid nematodes in a subarctic lake - Braicovich, Paola Elizabeth (2016)
In Takvatn, a subarctic lake in northern Norway, 35 of 162 three-spined sticklebacks examined were infected with 106 specimens of third-stage larvae of Philonema oncorhynchi. The prevalence and mean intensity of P. oncorhynchi were 10 % and 2.0 in 2013 and 24 % and 3.0 in 2014, respectively. A single specimen of Cystidicola farionis was found in an additional sample. While the latter is considered an accidental infection, three-spined sticklebacks may function as paratenic hosts of P. oncorhynchi, potentially enhancing its transmission to salmonids due to their central role in the lacustrine food web of this subarctic lake.